Challenges Ahead for a Rational Analysis of Vitamin D in Athletes - Araujo, Pedro; Méndez-Dávila, Cioly (Frontiers in Nutrition, 2021)
Vitamin D is an essential vitamin for the normal formation of bones and calcium absorption. It is synthetized in our body by sunlight exposure and obtained by consuming foods rich in vitamin D (e.g., fatty fish, eggs yolk, dairy products, etc). Its benefits on the health and performance of athletes are well documented. This article outlines some analytical challenges in relation to the analytical quantification of vitamin D for optimal intake, namely, comprehensive study of the assays variability before categorizing any method as golden standard; assurance of sample comparability to draw meaningful correlations; revision of the intake guidance on the basis of appropriate statistical power analysis; and implementation of rational strategies for preventing the underlying mechanism of preanalytical factors. Addressing these challenges will enable an effective management of the vitamin D in the sport sector.